2020
DOI: 10.1001/jamaoncol.2020.2045
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sedentary Behavior With Cancer Mortality in Middle-aged and Older US Adults

Abstract: IMPORTANCESedentary behavior is associated with several health outcomes, including diabetes, cardiovascular disease, and all-cause mortality. Less is known about the association between objectively measured sedentary behavior and cancer mortality, as well as the association with physical activity.OBJECTIVE To examine the association between accelerometer-measured sedentary behavior (total volume and accrual in prolonged, uninterrupted bouts) and cancer mortality. DESIGN, SETTING, AND PARTICIPANTSA prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 32 publications
4
69
0
2
Order By: Relevance
“…56) However, replacing 30 minutes of sedentary time with LIPA reduced the cancer mortality by 8% (HR, 0.92; 95% CI, 0.86-0.97) and replacing it with MVPA reduced it by 31% (HR, 0.69; 95% CI, 0.48-0.97). 56)…”
Section: The Attenuative Effect Of Physical Activity On Sedentary Lifmentioning
confidence: 99%
See 1 more Smart Citation
“…56) However, replacing 30 minutes of sedentary time with LIPA reduced the cancer mortality by 8% (HR, 0.92; 95% CI, 0.86-0.97) and replacing it with MVPA reduced it by 31% (HR, 0.69; 95% CI, 0.48-0.97). 56)…”
Section: The Attenuative Effect Of Physical Activity On Sedentary Lifmentioning
confidence: 99%
“…A recently published study showed that sedentary behavior was independently associated with cancer mortality risk, where a higher sedentary time led to a greater cancer mortality risk. In this study, the individuals in the top 1/3 of the sedentary group showed a substantially higher cancer mortality risk than those in the bottom 1/3 (adjusted HR, 1.52; 95% CI, 1.01–2.27) [ 56 ]. However, replacing 30 minutes of sedentary time with LIPA reduced the cancer mortality by 8% (HR, 0.92; 95% CI, 0.86–0.97) and replacing it with MVPA reduced it by 31% (HR, 0.69; 95% CI, 0.48–0.97) [ 56 ].…”
Section: Sedentary Lifestyles and Physical Activitymentioning
confidence: 99%
“…One area of research that has increased dramatically focuses on muscle mass and strength related to cancer treatment and prevention [18][19][20][21][22][23][24][25][26][27][28]. Caan and associates in 2018 showed that women with non-metastatic breast cancer had 41% better chance of surviving with a healthier muscle mass compared to sarcopenic non-metastatic breast cancer patients [18].…”
Section: Research Cancer (Heading 2 Intechopen)mentioning
confidence: 99%
“…The figures also show after the 40-49 age group there is a rapid decrease in absolute strength which supports the concept of loss of muscle mass and strength with aging along with an increase in sedentary lifestyles. Interestingly, the youngest age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) had the greatest deficit for the shoulder and knee strength when compared to the three age groups between 30 and 59. This is a reflection on the sedentary lifestyles found in children and youth which then carries over into industry.…”
Section: Descriptive Data For Males and Females (Means ± Sd)mentioning
confidence: 99%
“…Published in JAMA Oncology , the study was the first to examine the connection and show a strong association between these 2 objective measures 1 . Furthermore, the amount of time that a person spends sitting before a cancer diagnosis is predictive of the time to cancer death, notes lead author Susan Gilchrist, MD, a professor of clinical cancer prevention at MD Anderson.…”
mentioning
confidence: 99%